2021
DOI: 10.1186/s43055-021-00514-0
|View full text |Cite
|
Sign up to set email alerts
|

Can DWI-MRI be an alternative to DCE-MRI in the diagnosis of troublesome breast lesions?

Abstract: Background Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has always been a problem solver in troublesome breast lesions. Despite its many advantages, the encountered low specificity results in unnecessary biopsies. Diffusion-weighted MRI (DW-MRI) is a well-established technique that helps in characterizing breast lesions according to their water diffusivity. So this work aimed to assess the diagnostic performance of DW-MRI in troublesome breast lesions and see if it can replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
2
7
1
Order By: Relevance
“…That was superior to the sensitivity and specificity reported by Mehnati et al in [8], which were 30-60 and 40-80, respectively. Nevertheless, the results in the current study were in reproachment to the findings recorded by Eisa et al in [9] and Hashem et al [7] in their studies, who demonstrated a specificity of 74% and 80%, with sensitivity of 68% and 73%, respectively. These paralogisms in the mammography are mainly attributed to the dense breast cases (ACR III and IV), where the fibro glandular tissue almost conceal any breast lesions, yet aided by ultrasound; their sensitivity and specificity to detect and characterize lesions are relatively higher.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…That was superior to the sensitivity and specificity reported by Mehnati et al in [8], which were 30-60 and 40-80, respectively. Nevertheless, the results in the current study were in reproachment to the findings recorded by Eisa et al in [9] and Hashem et al [7] in their studies, who demonstrated a specificity of 74% and 80%, with sensitivity of 68% and 73%, respectively. These paralogisms in the mammography are mainly attributed to the dense breast cases (ACR III and IV), where the fibro glandular tissue almost conceal any breast lesions, yet aided by ultrasound; their sensitivity and specificity to detect and characterize lesions are relatively higher.…”
Section: Discussionsupporting
confidence: 86%
“…The main symptoms of the included patients in the study were asymmetry in breast size (n = 2/60 3.3%), lump (n = 34/60 56.7%), mastalgia (n = 20/60, 33.3%), and nipple discharge (n = 4/60, 6.7%). On the other hand, in the study conducted by Hashem et al [7], 52.3% of 86 patients had breast lumps (n = 45/86), 7% had inflammatory symptoms (n = 6/86), and 40.7% had postoperative follow-up (n = 35/86).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…For screening and specialized incompatible cases, it has even been postulated that DCE-MRI may be omitted, and precise diagnostic accuracy can be achieved using DWI-MRI [27]. Furthermore, DWI sequences are important for not only confirming lesions and distinguishing malignant lesions from benign lesions, but also for achieving the medium-term goal of reducing or even eliminating the need for intravenous contrast-agent administration while maintaining high diagnostic accuracy [28,29]. To enable international comparability in diagnostics by standardizing MRI-breast-examination methods and techniques, the development of new, clinically relevant, and validated techniques by consensus is crucial [1,30].…”
Section: Discussionmentioning
confidence: 99%